Online Learning Amidst Covid 19 Pandemic Disruption: EFL Lecturers and Students’ Classroom Interaction - Putri Erwani; Sofendi; Soni Mirizon (JEELS (Journal of English Education and Linguistics Studies), 2022)
Due to Covid 19 pandemic, for the last two years face-to-face classroom instruction in all education level has been migrated to online mode which may be conducted elsewhere outside of the face-to-face classroom context. This shifting brings a new trend in the classroom interaction between teachers and students. This study aims at finding out types of classroom interaction the lecturers and students do in running online learning in a public university in Palembang. Qualitative method with a case study design was employed in this study. The participants of this study were the lecturers and students who taught and learned speaking subject in English education study program at one public university. The data were collected through observation and interview to the EFL lecturers and students. The data were analyzed by using thematic analysis through coding process. The findings revealed that there were four kinds of classroom interactions commonly happened during the online learning activities, viz. Student-instructor, student-student, student-content, and student-interface interactions.